2011
DOI: 10.3109/00207454.2011.608139
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Hypersensitivity: Evidence for a Novel Neurological Syndrome

Abstract: EMF hypersensitivity can occur as a bona fide environmentally inducible neurological syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 17 publications
4
25
0
4
Order By: Relevance
“…For example, the calcarine sulcus (cluster 2) is considered to be the primary visual cortex [Engel et al, ], and the left superior frontal gyrus is thought to contribute to working memory [Boisgueheneuc et al, ]. Previous studies provided evidence for electromagnetic hypersensitivity, which includes visual disturbances [McCarty et al, ] and acute EMF exposure, which could affect human working memory [Zubko et al, ]. Our results provided more support for these phenomena.…”
Section: Discussionsupporting
confidence: 68%
“…For example, the calcarine sulcus (cluster 2) is considered to be the primary visual cortex [Engel et al, ], and the left superior frontal gyrus is thought to contribute to working memory [Boisgueheneuc et al, ]. Previous studies provided evidence for electromagnetic hypersensitivity, which includes visual disturbances [McCarty et al, ] and acute EMF exposure, which could affect human working memory [Zubko et al, ]. Our results provided more support for these phenomena.…”
Section: Discussionsupporting
confidence: 68%
“…While there is little public awareness of this problem in the United States, a New York Court determined that microwave sickness (the Cold War name for EHS) was a compensable disability as an "occupational radiation disease" in a 1982 court case (15). Moreover, an American literature review from 1998 provided 10 citations of United States occupational and clinical cases dating back to 1953 (16 (18). In 2010, an American literature review (19) cited a German study, which found that > 10% of the population there reported symptoms of EHS/EIS (20).…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that a recent publication, in International Journal of Neuroscience, from the Department of Neurology, Louisiana State University Health Sciences Center in Shreveport, concluded that EHS can occur as a bona fide environmentally inducible neurological syndrome [7]. The study sought direct evidence that acute exposure to environmental-strength EMFs could induce somatic reactions (i.e., EHS).…”
Section: Microappsmentioning
confidence: 98%